The relationship between interpersonal conflict, organizational citizenship behaviour and turnover intention among workers in Malaysia - Chu, Kai Xin; Wye, Sheng Khang (2023)
Turnover intention is a crucial issue that brings numerous harms to the organization. Hence, the present research investigated the relationship between interpersonal conflict, organizational citizenship behaviour (OCB) and turnover intention among workers in Malaysia. This study utilized cross-sectional survey design. Three instruments were involved in the online self-report questionnaire, including 4-Item Interpersonal Conflict at Work Scale, 10-Item Short Version of the Organizational Citizenship Behaviour Checklist and 4-Item Turnover Intention Scale. Upon received ethical clearance approval, informed consent was included in the questionnaire and Qualtrics link were sent to participants through several social media platforms. Besides, purposive sampling method was employed since there were several inclusion criteria, which are Malaysian workers that currently working in Malaysia and having at least one year of working experience. A total of 208 Malaysian workers aged between 19 to 57 (M = 28.48 years; SD = 7.77 years), with 56.70% were females (n = 118) and 43.40% were males (n = 90), were participated in this research. The outcomes of study showed that interpersonal conflict was positively correlated with turnover intention. Interpersonal conflict also positively predicted turnover intention. Similarly, OCB was negatively correlated with turnover intention. OCB also negatively predicted turnover intention. The implications and applications of the present study were discussed. The findings not only enriched the literature and filled the research gap, but also assisted employers and other relevant authorities in designing interventions to reduce turnover intention.